Using laser-induced Coulomb explosion of aligned chiral molecules to determine their absolute configuration - Christensen, L; Nielsen, J; Slater, C; Lauer, A; Brouard, M; Stapelfeldt, H (American Physical Society, 2015)
The absolute configuration of chiral molecules in the gas phase is determined by femtosecond laser-induced Coulomb explosion and recording of the emission direction of critical ionic fragments. The spatial orientation of the 3,5-dibromo-3′,5′-diflouro-4′-cyanobiphenyl molecules studied is determined by a combination of laser-induced alignment and time-of-flight measurement of F+ ion recoils. Hereby, the enatiomeric state of the molecules could be uniquely identified through analysis of the correlation of the angular distribution of F+ and Br+ ions. The method will apply to a range of molecules and allow imaging of chiral changes on ultrafast time scales.